2002
DOI: 10.1007/s101510200005
|View full text |Cite
|
Sign up to set email alerts
|

Sacrococcygeal pilonidal sinus disease with Limberg flap repair

Abstract: Sacrococcygeal pilonidal sinus disease affects younger persons, resulting in long-term loss of productive power. It also has a high rate of morbidity because there is no standard treatment approved by all surgeons. In this study, early and late results of 85 cases treated with excision and Limberg flap in our clinic were investigated. The patients were followed for 9-120 months. The complication rate was 4.7% and the long-term relapse rate was 3.5: Insufficient personal hygiene and inadequate excision were the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
1
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 14 publications
(37 reference statements)
2
72
1
2
Order By: Relevance
“…Literature has documented a recurrence rate of 0-3% for Limberg flap against a significantly high recurrence of 7-42% for primary closure. 26,[33][34][35][36][37][38] Our study also three recurrences in primary closure and nil in case of Limberg flap group and nil in 3 rd group where healing was by secondary intention. Our results also support those patients in primary closure group walked freely without significant pain after a relatively longer period than patients treated with flaps because of the tension created by the primary suture technique.…”
supporting
confidence: 62%
“…Literature has documented a recurrence rate of 0-3% for Limberg flap against a significantly high recurrence of 7-42% for primary closure. 26,[33][34][35][36][37][38] Our study also three recurrences in primary closure and nil in case of Limberg flap group and nil in 3 rd group where healing was by secondary intention. Our results also support those patients in primary closure group walked freely without significant pain after a relatively longer period than patients treated with flaps because of the tension created by the primary suture technique.…”
supporting
confidence: 62%
“…So, looking that way one expects flap procedures to combat the disease recurrence better than excision with simple closure, keeping in view extensive dissection of the sinus tracts and the shallower cleft that flap procedures provide. Literature has documented a recurrence rate of 0-3% [2][3][4][5][6] for Limberg flap against a significantly high recurrence of 7-42% [7,8] for primary closure. Outcome of our study in terms of recurrence of the sinus is the same as reported by other studies, namely, three recurrences for the primary closure group against zero recurrence of the Limberg flap group.…”
Section: Discussionmentioning
confidence: 99%
“…The latter technique results in significantly higher recurrence rates as compared to the former (7-40% and 0-3%, respectively) (5-7). Limberg technique seems to have the lowest wound related complication and recurrence rate (8)(9)(10)(11). However, excision and primary midline suturing has been the most frequently used method with the highest postoperative complication and recurrence rates (12).…”
Section: Introductionmentioning
confidence: 99%